Analisis Kesalahan Penggunaan Ejaan dan Tanda Baca dalam Karangan Narasi Dikaitkan dengan Sikap Tanggung Jawab Siswa - Riska Hiro Santi; Siti Halidjah; Bistari Bistari; Hery Kresnadi; Suparjan Suparjan (AS-SABIQUN, 2022)
This study aims to describe the use of spelling and punctuation errors that are high, medium, and low in narrative essays associated with the attitude of responsibility in fifth grade students of SD Negeri 30 Pontianak Selatan. This study uses a descriptive qualitative approach. The data analysis technique uses the Miles and Huberman model which includes for stages, namely data collection, data reduction, data presentation, and drawing conclusions. The results of responsibility based on the error rate, namely at high errors because students did not understand the use of proper spelling and punctuation, for moderate errors because there were students who did not pay attention to the use of spelling and punctuation. Correct in composing, and far low errors, students already know the use of proper spelling and punctuation, but there are still few errors found, and it is associated with an attitude of responsibility based on the error rate, student with high, medium, and low error rates for their attitudes it’s all good.